The steroid receptor coactivator SRC-3 (p/CIP/RAC3/AIB1/ACTR/TRAM-1) is required for normal growth, puberty, female reproductive function, and mammary gland development - Xu, Jianming (National Academy of Sciences, 2000)
Steroid receptor coactivator-3 (SRC-3) is a coactivator of nuclear receptors in the SRC family as assayed in vitro. Here, we show that mouse SRC-3 is expressed in a tissue-specific fashion and distributed mainly in the oocytes, mammary glands, hippocampus, olfactory bulb, smooth muscle, hepatocytes, and vaginal epithelium. Genetic disruption of SRC-3 in mice results in a pleiotropic phenotype showing dwarfism, delayed puberty, reduced female reproductive function, and blunted mammary gland development. Hormonal analysis indicates that SRC-3 plays a role in both the growth hormone regulatory pathway and the production of estrogen, which may explain the observed phenotypes. These results suggest that the physiological role of SRC-3 is different from that of SRC-1 and prove the diversity among coactivator family members.